Assessing the remobilization of Antimony in sediments by DGT: A case study in a tributary of the Three Gorges Reservoir. (July 2016) - Gao, Li; Gao, Bo; Zhou, Huaidong; Xu, Dongyu; Wang, Qiwen; Yin, Shuhua
Abstract: The Three Gorges Reservoir (TGR) is one of the world's largest man-made hydropower projects, which has posed great challenges to the aquatic environment of the Yangtze River since the impoundment of water. As a non-essential toxic metalloid, information on the bioavailability of Antimony (Sb) in TGR sediments is lacking. Four sediment cores were collected from a tributary and the mainstream in the TGR to investigate the distribution and remobilization of Sb using the diffusive gradients in thin films (DGT) technique. The results showed that the concentrations of Sb obtained by DGT (CDGT -Sb) at all of the sampling stations were low (below 0.30 μg/L), compared to the relatively high Sb concentrations in the sediments. The lateral and vertical distributions of CDGT -Sb revealed different tendencies in overlying water and sediments at all of the sampling sites in the TGR, which may be attributed to anthropogenic impacts, the heterogeneity of sediments and the unevenness of the sediment-water interface (SWI) during the deployment of DGT probes. In addition, CDGT -Sb in the surface sediments were lower than those in the overlying water, and concentration gradients were found near the SWI, demonstrating that Sb has the potential to diffuse from the overlying water into the sediment. In the sediment cores, different peaks were discovered in the DGT probes and the remobilization of Sb simultaneously appeared in the vicinity of −10 cm. Correlation analysis showed that CDGT -Sb had no or negative correlation with CDGT -Fe and CDGT -Mn in all of the DGT probes, suggesting that the release of Sb was unassociated with Fe and Mn in the sediments in the study area. Highlights: We determined the DGT-labile Sb in sediment cores from a tributary in TGR. There was obvious lateral variation of DGT-labile Sb in the upstream and downstream. Concentration gradients were found in the vicinity of the sediment-water interface. "Peak areas" phenomenon appeared simultaneously in the vicinity of −10 cm. Abstract : Low CDGT -Sb was found and "peak areas" phenomena appeared simultaneously in the vicinity of −10 cm in tributary sediment cores in TGR.